Strength of Axially Loaded Cold-Formed Steel Z Profiles Stub Columns - Eko Juwanto; Andy Prabowo; Siswadi (Journal of Civil Engineering and Planning (JCEP), 2026)
This study evaluates the axial behavior of G450 cold-formed steel Z-section stub columns through tensile and axial compression tests. The results indicate that the material exhibits no distinct yield plateau and is dominated by strain hardening behavior. Axial compression tests indicate that the capacity ranges from 136–364 MPa, with failure modes governed by local buckling. The analysis identifies plate slenderness as the primary parameter influencing axial capacity and contributing to deviations from theoretical predictions. These findings highlight limitations in conventional design approaches and provide a basis for improving axial capacity prediction of cold-formed steel Z-sections.